If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -6 + y + 26 = 6y + 20 + -4y Reorder the terms: -6 + 26 + 3y + y = 6y + 20 + -4y Combine like terms: -6 + 26 = 20 20 + 3y + y = 6y + 20 + -4y Combine like terms: 3y + y = 4y 20 + 4y = 6y + 20 + -4y Reorder the terms: 20 + 4y = 20 + 6y + -4y Combine like terms: 6y + -4y = 2y 20 + 4y = 20 + 2y Add '-20' to each side of the equation. 20 + -20 + 4y = 20 + -20 + 2y Combine like terms: 20 + -20 = 0 0 + 4y = 20 + -20 + 2y 4y = 20 + -20 + 2y Combine like terms: 20 + -20 = 0 4y = 0 + 2y 4y = 2y Solving 4y = 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 4y + -2y = 2y + -2y Combine like terms: 4y + -2y = 2y 2y = 2y + -2y Combine like terms: 2y + -2y = 0 2y = 0 Divide each side by '2'. y = 0 Simplifying y = 0
| 6(-2x+2)=48 | | graphy=4x+9 | | ln(x-1)ln(x+1)=0 | | 6(c-3)=7(c-5) | | 20(t-3)=80 | | (x^2-2xy)dy-(y^2-2xy)dx=0 | | 6(2x+6)=84 | | (2sqrtx+y)dx+xdy=0 | | 42=3(3m-4) | | (2x-y)dx+(2x+y)dy=0 | | 3(2b-2)=6(1+3b) | | (2xy-y^2)dx-x^2dy=0 | | C/d=x | | .50x+.75y=20 | | -6r-29=-5(2+5r) | | 6y+1=-13 | | 11(x-6)=-11 | | r=(7+B)m | | 8x+2=5x-6 | | 11(x-6)=11 | | -4(1-4v)-v=-4-2v | | 5(x-6)=-10 | | -(3n-5)=-5n-7 | | lnx*sin^3*y*dx+x*cosy*dy=0 | | z^2+6z+20=0 | | 5a-5=6(-4a+4) | | (x-y)ydx-x^2dy=0 | | 16lw=v | | 2x^2-3xy-2y^2-2x-11y-12=0 | | 5-3x=14+2x | | 5x-3(x-5)+9(y-5)= | | x^4-9x+7=0 |